Genome-wide association study identifies common variants associated with pharmacokinetics of psychotropic drugs. (August 2015) - Athanasiu, Lavinia; Smorr, Lisa-Lena H; Tesli, Martin; Røssberg, Jan I; Sønderby, Ida E; Spigset, Olav; Djurovic, Srdjan; Andreassen, Ole A
Individual variation in pharmacokinetics of psychotropic drugs, particularly metabolism, is an important factor to consider in pharmacological treatment in psychiatry. A large proportion of this variance is still not accounted for, but evidence so far suggests the involvement of genetic factors. We performed a genome-wide association study (GWAS) with concentration dose ratio (CDR) as sub-phenotype to assess metabolism rate of psychotropic drugs in a homogenous Norwegian sample of 1334 individuals diagnosed with a severe mental disorder. The GWAS revealed one genome-wide significant marker (rs16935279, p -value=3.95×10 −10, p perm =7.5×10 −4 ) located in an intronic region of the lncRNA LOC100505718 . Carriers of the minor allele have a lower metabolism rate of antiepileptic drugs compared to major allele carriers. In addition, several nominally significant associations between single nucleotide polymorphisms (SNPs) and CDR for antipsychotic, antidepressant and antiepileptic drugs were disclosed. We consider standardised CDR to be a useful measure of the metabolism rate of a drug. The present findings indicate that common gene variants could affect the metabolism of psychotropic drugs. This warrants further investigations into the functional mechanisms involved as it may lead to identification of predictive markers as well as novel drug targets.